2013
DOI: 10.1007/s13181-013-0320-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features, Testing, and Management of Patients with Suspected Prosthetic Hip-Associated Cobalt Toxicity: a Systematic Review of Cases

Abstract: Safety concerns regarding cobalt-containing metal alloy hip prosthetics (Co-HP) have resulted in product recalls, a medical device alert, and issuance of guidance for clinicians. Recently, cases of suspected prosthetic hip-associated cobalt toxicity (PHACT) from Co-HP have been reported. Although little is known about suspected PHACT, these patients may be referred to medical toxicologists for evaluation and management recommendations. We searched MEDLINE, EMBASE, and unpublished abstracts from toxicology scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 43 publications
0
65
0
Order By: Relevance
“…33 More recently, case reports and small series have reported cardiomyopathy related to failure of MoM implants. 7,[35][36][37][38][39] However, there were < 30 cases in total and these patients had extreme levels of circulating metal ions. Prentice et al 40 performed a cross-sectional observational study of systemic complications and found a 5% lower ejection fraction in 35 patients with MoM resurfacing implants compared with patients with conventional arthroplasties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 More recently, case reports and small series have reported cardiomyopathy related to failure of MoM implants. 7,[35][36][37][38][39] However, there were < 30 cases in total and these patients had extreme levels of circulating metal ions. Prentice et al 40 performed a cross-sectional observational study of systemic complications and found a 5% lower ejection fraction in 35 patients with MoM resurfacing implants compared with patients with conventional arthroplasties.…”
Section: Discussionmentioning
confidence: 99%
“…The failure of these devices has led to many patients subsequently undergoing early revision. [5][6][7][8] Corrosion and wear of MoM implants, which are composed of cobalt-chromium alloy, can result in the release of particulate debris and metal ions into the circulation. Alongside localized effects, MoM prostheses have been associated with systemic complications such as cardiotoxicity and mortality.…”
Section: Cite This Article: Bone Joint J 2018;100-b:20-7mentioning
confidence: 99%
“…Some papers report the physical effects of metallosis following MoM implants [2, 10, 11, 14, 24, 28, 29]. To the best of our knowledge there are no papers specifically describing psychiatric symptoms following MoM implants, but there is a case report indicating neurological problems associated with cobalt and chromium toxicity [27].…”
Section: Introductionmentioning
confidence: 99%
“…Prior to this research there have been only case reports on people with MoM prostheses who have developed heart failure [4]. The results have implications for people who have received ASR XL prostheses and potentially also other LH MoM prostheses.…”
Section: Discussionmentioning
confidence: 94%